Early-life growth hormone treatment to offspring of undernourished mothers alters metabolic parameters in primary adipocytes in adulthood. (February 2014) - Reynolds, C. M.; Li, M.; Gray, C.; Vickers, M. H.
Abstract Maternal undernutrition (UN) is associated with the development of obesity and metabolic complications in adult offspring. This study investigated the impact of preweaning growth hormone (GH) treatment on adipocyte functionality in adult male offspring. Sprague-Dawley rats were assigned either standard (C) or undernourished (UN) diet (50% ad libitum) throughout gestation. Postnatal day 3–21, male C/UN pups received either saline (CS, UNS) or GH (2.5 µg/g/d; CGH, UNGH) by subcutaneous injection. Primary adipocytes were isolated following the collagenase digestion of adipose tissue. Primary adipocytes from UN offspring had significantly increased the secretion of pro-inflammatory cytokines accompanied by increased cytokine/cytokine receptor expression. This correlated with increased TLR4/NF-κB signaling. While increased inflammatory potential was not observed in adipocytes derived from UNGH offspring, there was a clear alteration in the expression of genes relating to carbohydrate and lipid metabolism along with nutrient transporters. Overall, preweaning GH treatment alters detrimental patterns of development, which predispose UN offspring to obesity and insulin resistance.